Disentangling a Neotropical pest species complex: genetic diversity and population structure of the native rice stink bug Oebalus poecilus and the invasive O. ypsilongriseus. Issue 3 (18th November 2022) - Vieira, Juliana L.; de Oliveira, Luiz O.; Barrigossi, José Alexandre F.; Guedes, Raul Narciso C.; Smagghe, Guy; Maebe, Kevin
Abstract: Background: A first step in any pest management initiative is recognizing the existing problem – identifying the pest species and its abundance and dispersal capacities. This is not simple and even more challenging when insidious (invasive) species are involved constituting a pest complex. Understanding a species' population diversity and structure can provide a better understanding of its adaptation and relative pest potential. Such is the need for the native rice stink bug Oebalus poecilus and the invasive O. ypsilongriseus in low and high flatlands of South America. Results: The genetic structure differed between both rice stink bug species ( F ST  = 0.157, P  = 0.001), where 84% of the overall genetic variability takes place within species and three genetic groups were recognized through Bayesian approach ( K  = 3). Oebalus poecilus exhibited slightly higher genetic diversity ( H E  = 0.253) and structuring ( F ST  = 0.050, P  = 0.001) than the invasive O. ypsilongriseus ( H E  = 0.211; F ST  = 0.038, P  = 0.013). Nonetheless, only the former exhibited significant correlation between genetic and geographic distances ( r  = 0.48, P  = 0.013). Conclusion: Despite the pointed peculiarities, the obtained results indicate overlap in both species' occurrence and similar genetic structure allowing for a compound problem to be dealt with as the complex requires managing without, as yet, a prevailing species or a niche specialization. © 2022 Society of Chemical Industry. Abstract : Populations of both stink bug species exhibited similar levels of diversity and structuring. The existence of an intermediary genetic group overlapping the species is suggestive for added adaptation and range expansion, which also deserves attention.